2022
DOI: 10.1371/journal.pcbi.1010166
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of hypoxic regions distant from occlusions in cerebral penetrating arteriole trees

Abstract: The microvasculature plays a key role in oxygen transport in the mammalian brain. Despite the close coupling between cerebral vascular geometry and local oxygen demand, recent experiments have reported that microvascular occlusions can lead to unexpected distant tissue hypoxia and infarction. To better understand the spatial correlation between the hypoxic regions and the occlusion sites, we used both in vivo experiments and in silico simulations to investigate the effects of occlusions in cerebral penetrating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…These findings raise the question of how can blocking a small fraction of capillaries (∼1.82-3.64% in diabetic mice), appreciably affect cognition? Although our stalling estimates are largely comprised of short-lived stalls lasting at least 6.5s, experimental and computational data suggest that 2-4% of stalled capillaries can lead to a 5-20% decrease in cerebral blood flow, which also improved cognition in Alzheimer mice 14, 82 . It is important to note that our microsphere experiments revealed that diabetes also increased the fraction of long-lived (∼3 day) capillary obstructions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings raise the question of how can blocking a small fraction of capillaries (∼1.82-3.64% in diabetic mice), appreciably affect cognition? Although our stalling estimates are largely comprised of short-lived stalls lasting at least 6.5s, experimental and computational data suggest that 2-4% of stalled capillaries can lead to a 5-20% decrease in cerebral blood flow, which also improved cognition in Alzheimer mice 14, 82 . It is important to note that our microsphere experiments revealed that diabetes also increased the fraction of long-lived (∼3 day) capillary obstructions.…”
Section: Discussionmentioning
confidence: 99%
“…It thus also enables quantitative comparisons to be made between different conditions: for example, the study by Gkontra et al (2019), which, although in the porcine coronary microcirculation, showed that the measured permeability tensor dynamically changes in the seven days following myocardial infarction. Computational modelling in the cerebral circulation has also shown that the permeability changes in response to microthrombi (with the changes dependent upon the type of clot and the choice of thrombectomy procedure), El-Bouri et al (2021), and these changes have been recently validated in animal models, Xue et al (2021) and Xue et al (2022). Gaining a quantitative understanding of changes in the permeability tensor is a concise way of providing a better understanding of the response both to ischaemia and to therapies such as mechanical thrombectomy.…”
Section: Reconstruction Of the Microvasculaturementioning
confidence: 99%
“…The model has been utilised for the simulation of brain osmotherapy and haemorrhagic transformation after stroke and validated with clinical data [33,34]. The present study sets out to extend computational brain models developed in the In Silico Clinical Trials for the Treatment of Acute Ischaemic Stroke (INSIST) project [28,[35][36][37] by incorporating a contact mechanics solver to simulate oedema with large deformations and ventricle collapse and then to investigate factors such as patient brain geometry, the severity of BBB damage and types of oedemas that can affect the ICP-MLS relation. Once a reliable model is established, it will help to sharpen the focus of resource-intensive clinical studies, and thus lower the associated (often very high) costs.…”
Section: Plos Computational Biologymentioning
confidence: 99%